EFFECTIVITY IMPROVEMENT OF HYBRID PROJECT MANAGEMENT WATER-SCRUM-FALL WITH SIX SIGMA IMPLEMENTATION - Aria Setyoko; Teguh Rahardjo; Nur Fitriani Anita (LPPM Nusa Mandiri, 2024)
In software development projects there is continuous development aimed at increasing the efficiency and effectiveness of the team in providing software quality and customer satisfaction. The problem is that many projects are planned using a waterfall approach by clients, therefore some tools are needed to balance this situation. This research aims to evaluate the effectiveness of hybrid methodologies in software development by uncovering the use of a combination of Waterfall and Agile Scrum methodologies with the application of Six Sigma. This hybrid methodology was deemed suitable for combining the plan- and contract-based characteristics of Waterfall with the flexibility and rapid iteration of Agile Scrum. The use of Six Sigma is used to focus on change, assist in systematically identifying and correcting process problems, and process improvement. In research methods, sample teams run different methodologies on similar software projects. Hybrid project management is carried out by applying the Waterfall approach in planning and contracts. At the same time, each phase in Waterfall is iterated using Agile Scrum to ensure flexibility and adaptability. The research results found that this hybrid method can increase team efficiency, reduce development cycle time, detect higher defects in each sprint, increase the final quality of the software, and finally increase the Sigma Index with a team comparison of σ=3.22 and σ= 3.11 and higher compared to teams that only use Agile-Scrum. In conclusion, the integration of Waterfall, Agile Scrum, and Six Sigma can be an effective strategy to face the challenges of modern software development.